2008
DOI: 10.1016/j.jcrs.2008.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of hyaluronidase 75 IU as an adjuvant to mepivacaine for retrobulbar anesthesia in cataract surgery

Abstract: The addition of hyaluronidase to mepivacaine for retrobulbar anesthesia in cataract surgery enhanced the safety of the surgical procedure due to more complete akinesia and quicker onset of complete anesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 15 publications
(12 reference statements)
0
17
0
2
Order By: Relevance
“…Abelson et al 5 used 60 IU ml −1 of hyaluronidase in 5 ml and again found a rapid onset with superior akinesia scores in the hyaluronidase group. Remy6 also showed improved onset, akinesia and analgesia with 75 IU.…”
Section: Hyaluronidasementioning
confidence: 85%
“…Abelson et al 5 used 60 IU ml −1 of hyaluronidase in 5 ml and again found a rapid onset with superior akinesia scores in the hyaluronidase group. Remy6 also showed improved onset, akinesia and analgesia with 75 IU.…”
Section: Hyaluronidasementioning
confidence: 85%
“…10,23,[38][39][40][41][42] The clinical safety and tolerability of hyaluronidase, which was first reported by Burket and Gyorgy in 1949, 38 have been established further with over 6 decades of use. 10,23,[39][40][41][42] Clinical history demonstrates the increased dispersion and faster absorption of a broad range of drugs and fluids administered with hyaluronidase products. 10,23,[38][39][40][41][42][43][44] With rHuPH20, for example, Thomas and colleagues 45,46 have demonstrated an accelerated PK profile of SC morphine coadministered with rHuPH20 compared with SC morphine alone, with earlier and greater peak exposure and comparable total bioavailability.…”
Section: History Of Hyaluronidase Administrationmentioning
confidence: 99%
“…In a traditional subcutaneous injection, insulin absorption is diffusion limited; insulin hexamers must first diffuse away from the site of injection to dissociate and become available for absorption. 41 Thus, the absorption of insulin is affected by both insulin concentration and dose (Figure 2). 48 High concentrations and high doses are absorbed more slowly because of diffusion limitations.…”
Section: Mechanisms Underlying Absorption Kinetics Of Subcutaneously mentioning
confidence: 99%
“…al, 2001;Hamada et al, 2005;Remy et al, 2008;Pacella et al, 2013) bem como a diminuição de efeitos adversos pós-anestesia (Hamada et al, 2005), sendo utilizada quase que exclusivamente com sucesso para anestesia oftalmológica. Os estudos mais recentes em oftalmologia testam anestésicos diversos, alcalinizados ou não, mas todos utilizam a HIA como padrão de comparação com novos fármacos ou técnicas (Islam et al, 2012;Gordazi et al, 2011;Pacella et al, 2010;Jaichandran et al, 2010).…”
Section: Discussionunclassified
“…As vias de administração da HIA podem ser tópica, intradérmica ou intramuscular, não sendo aconselhável a aplicação via intravenosa, pois a enzima é rapidamente inativada no sangue (mecanismos ainda desconhecidos) (Mindel, 1978;Nicoll et al,, 1986;Thomson, 1988;Kallio et al, 2000;Remy et al, 2008) e peribulbares (Sarvela;Nikki, 1992;Dempsey et al, 1997;Hamada et al, 2005;Mantovani et. al, 2001;Pacella et al, 2013), e em outros, a redução da latência do bloqueio nervoso (Sarvela;Nikki, 1992;Nicoll et al, 1986) e diminuição de efeitos adversos pós-anestesia (Hamada et al, 2005).…”
Section: áCido Hialurônico E Hialuronidaseunclassified